Could antidepressants increase mood and immunity at the same time? - Lavergne, Francis; Jay, Therese M. (Frontiers in Psychiatry, 2025)
A review of scientific literature suggests that the use of antidepressants can be broadly extended to address various forms of stress and inflammation as an adjunctive therapy that enhances host resistance. While the effects of antidepressants on mood are well-documented in terms of their emotional, cognitive, and behavioral impacts, these aspects do not fully explain their cellular mechanisms of action. At the cellular level, antidepressants exert trophic effects that promote neurogenesis and synaptic connectivity. Studies demonstrate that antidepressants improve cell survival, enhance stem cell proliferation, and reduce danger perception (mood effects) in depressed patients and animal models of depression. These trophic properties highlight a deeper biological mechanism beyond their mood-related benefits. The acid sphingomyelinase (ASM) theory of mood offers a more compelling explanation of the cellular effects of antidepressants compared to the monoamine hypothesis. Antidepressants functionally inhibit the ASM enzyme, thereby reducing the production of ceramide, which directs cells toward increased survival, cytoprotection, and reproduction, as well as improved mood. This review also highlights research demonstrating that antidepressants enhance host resistance to infections, immunological challenges, stress, and depression. These findings support the potential use of antidepressants to bolster host resilience in scenarios involving infections, vaccinations, cellular aggression, stress, depression, and even aging.